Inter-regional conference, superior and talented student project, proposed action programs for 1960-61 - Northwestern Univ., Evanston, IL.; Northwestern Univ., Evanston, IL. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1960)
Descriptions of 18 different high schools across the country which are planning or had in operation programs for superior and talented students as of July 1960 are included. The states involved are California, Connecticut, Florida, Georgia, Idaho, Kentucky, Massachusetts, Oregon, South Carolina, Vermont, and Washington. Descriptions of the community and setting of the schools, personnel involved, cost of the program, the present guidance program, the existing superior student program, and the proposed superior student program for 1960-61 are included for each school.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academically Gifted; Conferences; Developmental Programs; High Schools; Honors Curriculum; Secondary Education; Talent; Illinois (Evanston)